An Empirical Investigation of the Performance of Fund Managers in Pakistan - Sanaullah Sanaullah; Amna Noor; Saleh Nawaz Khan; Muhammad Shahbaz Khan (iRASD Journal of Management)
This study aims to determine the stock selection ability and market timing ability of mutual fund managers, focusing on conventional funds and Islamic funds in Pakistan.  Although there has been significant growth in the number and assets of mutual funds in recent years, few studies measure the performance of mutual funds managers. The scarcity of existing literature motivates this study. In this study, two models are used to measure the stock selection and market timing on a sample of conventional mutual funds and Islamic mutual funds over 2010 and 2019 using annual returns. Overall, the results indicate that the performance study of conventional mutual funds and Islamic mutual funds indicates that manager performance is not superior in all three portfolios, i.e., conventional funds, Islamic funds, and overall funds in over sample period. This also indicates that both Conventional and Islamic fund managers do not outperform the market (KSE 100 index). Thus, there is a lack of market timing ability. Using Tranoy and mazuy and Jansen models found a lack of stock selection and market timing ability of mutual fund managers in Pakistani mutual funds. In this study, I have applied only two models to examine both the timing and selection ability of conventional and Islamic Pakistani equity funds. For future possibilities, the study suggests adopting several methods and approaches like the TMFF3 model and HM-FF3 model, making the study more comprehensive and accurate than this research.